Public Investment Efficiency in Sub-Saharan African Countries - Barhoumi, Karim; Maino, Rodolfo; Nikaein Towfighian, Shirin; Vu, Ha. (Washington, D.C. : International Monetary Fund, 2018)
There is significant room to improve public investment efficiency in sub-Saharan Africa. Investment in sub-Saharan African countries is lagging vis-a-vis peers such as emerging and developing Asia as well as Latin America and the Caribbean, and the region's infrastructure is perceived as being of relatively low quality. Improving the efficiency of sizable investment programs in the region could contribute to more solid economic growth and help achieve desired social priorities and development goals. Results point to some variability in public investment efficiency within the region. Comparing efficiency scores across country groups suggests that investment efficiency in sub-Saharan African oil exporters tends to be lower than in sub-Saharan African non-resource-intensive countries. Additionally, countries in East African Community (EAC) perform better than those in Central African Economic and Monetary Community (CEMAC) and West African Economic and Monetary Union (WAEMU). Stronger institutions could foster more efficient public investment. The regression results in this paper show a positive correlation between public investment efficiency and the quality of institutions, suggesting that devel-oping stronger institutions in sub-Saharan Africa could lead to a significant improvement in investment efficiency. This is particularly relevant for coun-tries with weak institutional quality, where governments may use capital spending as a vehicle for rent-seeking, leading to inefficient spending. Given the current drive for scaling up investment in sub-Saharan Africa, the task of improving institutions quickly should become a priority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet